4'-Fluoro-2'-hydroxy-acetophenone. - Rizal, M.R.; Ng, S.W. (International Union of Crystallography, 2008)
The title compound, C(8)H(7)FO(2), crystallizes as discrete mol-ecules, the conformation of which may be influenced by an intra-molecular hydr-oxy-carbonyl O-H⋯O hydrogen bond.